KONSELING DENGAN ABPK & PELAYANAN KB DALAM MENINGKATKAN PENGGUNAAN KONTRASEPSI JANGKA PANJANG (MKJP) PADA WUS DI WILAYAH PURI, KABUPATEN MOJOKERTO - NUNUK NURHAYATI; Noer Saudah; Elies Meilinawati; Partina (STIKES dan AKZI Karya Husada Kediri, 2023)
Family Planning Counseling with ABPK is a face-to-face conversation or interview between the client and the counselor, which is held on purpose, with the aim of helping the client make decisions that are in accordance with his conditions and wishes with the help of ABPK flipcharts. This ABPK flip sheet helps clients choose and use the most suitable family planning method according to their needs and with ABPK provides important information needed to provide quality services. The Long Term Contraceptive Method (MKJP) is part of the family planning program that regulates pregnancy and spacing. ideal age for giving birth These long-term contraception include: IUD, Implant, Vasectomy and Tubectomy. Based on BPS BKKBN East Java in 2022 MKJP KB participants were far fewer, namely 1,607,288 participants compared to non-MKJP KB, namely 4,123,035. The target in this community service activity is all women of childbearing age (WUS) who will have family planning with MKJP (Implans / IUDs) or plan to remove and reinstall MKJP which has been used by as many as 20 people. The implementation of community service for Free MKJP services is carried out on 2-28 June 2023 and the preparation of reports on community service activities and publishing journals is carried out until 30 July 2023. This community service activity uses the technique of providing ABPK counseling first and filtering with a wheel fit and after that just implementing the MKJP removal and installation service. The output of this community service activity is to increase the scope of MKJP services so as to assist government programs in terms of the success of the MKJP program. Keywords: Counseling, ABPK, MKJP